DIGITIZATION AND CULTURE (CASE STUDY ON LOCAL WISDOM-BASED CULTURE DEVELOPMENT THROUGH NEW MEDIA BY SAGANG FOUNDATION) - Fitria Mayasari (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2019)
The presence of media plays a very important role  to the growth and development of a culture, one of which is local  culture.  New  media  offers  a  variety  of  advantages  compared  to  traditional  media,  such  as  users  ability  to adjust  time.  The  demasification  of  new  media  also  affects  to  the  results  and  potential  of  the  use  of  new  media. Because the flow of information that takes place becomes more personal. Existing findings dissected the key ele- ment of successful in using new media as a strategy for political communication, campaigns and social movements. However, these efforts to use successful new media are often adhered by communities or institutions in large cities with adequate infrastructure and management. Therefore, it is interesting to see and analyze the use of new media in the field of cultural development from a non-profit organization. This study uses a case study approach to look at the strategy of developing local wisdom-based culture through new  media conducted by the Sagang Foundation. Regarding the results of research and analysis, it is known that the characteristics of individuals, organizations, and the  environment  contribute  to  the  results  of  the  use  of  the  media  carried  out  by  the  Sagang  Foundation.  These characteristics successfully  enhanced to the strategic results for organization in utilizing new media.Keywords: Digitization, Cultural, New Media, Sagang Foundation